Prediction of semitendinosus and gracilis autograft sizes for ACL reconstruction - (:unkn) unknown (SPRINGER, 2012)
The aim of this study was to predict the hamstring graft sizes prior to anterior cruciate ligament reconstruction surgery in adults by using preoperative magnetic resonance imaging (MRI). Fifty-one patients with anterior cruciate ligament rupture were prospectively evaluated. Diameter and cross-sectional areas of the gracilis and the semitendinosus tendons at two different levels were measured separately by preoperative MRI. In surgery, harvested gracilis and semitendinosus tendons were measured individually (2-stranded) and together (4-stranded) by using a graft sizing block. Radiological and operative sizes of the grafts were compared by Pearson's correlation test. ROC analysis was done to determine a possible cutoff value for the preoperative measurements. There were statistically significant correlations between the MR cross-sectional areas of gracilis, semitendinosus, gracilis + semitendinosus and intraoperative graft sizes of 2-stranded gracilis, 2-stranded semitendinosus and 4-stranded gracilis + semitendinosus tendons [P < 0.05]. No significant correlation was observed between the MR diameters of the gracilis, semitendinosus, gracilis + semitendinosus tendons and intraoperative graft sizes of 2-stranded gracilis, 2-stranded semitendinosus and 4-stranded gracilis + semitendinosus tendons [n.s]. Cross-sectional areas of the hamstring tendons in MR images can be used to estimate the sizes of hamstring grafts prior to anterior cruciate ligament reconstruction surgery which may be very helpful to predict possible graft insufficiencies and take precautions if needed. Level IV.
Keywords: Hamstring graft sizes; Magnetic resonance image; Prediction; ACL; Anterior crutiate ligament; ANTERIOR CRUCIATE LIGAMENT; CROSS-SECTIONAL AREA; GRAFT SIZE; FOLLOW-UP; TENDON; DIAMETER